A randomized controlled trial of eye shields and earmuffs to reduce pain response of preterm infants. Issue 3 (June 2015) - Aita, Marilyn; Goulet, Céline; Oberlander, Tim F.; Snider, Laurie; Johnston, Celeste
Abstract: The purpose of this study was to evaluate the pain response of 28–32 weeks gestational age preterm infants during a heel lance following a 4-h period where they had worn eye shields and earmuffs as a light and noise reduction intervention. A randomized controlled trial was conducted on 44 preterm infants recruited from four level III NICU. Heart rate and heart rate variability were collected continuously during the heel lance. At the end of the painful procedure, the time HR took to return to baseline was calculated. ANCOVA indicated that preterm infants who wore eye shields and earmuffs 4-h before the heel lance did not show a significant reduction in their pain response during the procedure in comparison to those who did not. Confounders such as handling in the hours preceding the painful procedure and the time it took to collect the blood might have influenced the results.